SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KINERJA KARYAWAN TERBAIK CV. BINTANG TERANG MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING - Fandy Fandy; Wasino Wasino; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
CV. BINTANG TERANG is a company engaged in distribution. CV. Bintang Terang requires a decision support system to determine the best employee performance in the company. The method that will be used is the Simple Additive Weighting (SAW) method. The SAW method is used to determine the best employee performance appraisal which later results from the calculation of the SAW method will be used as the best solution. Based on the research conducted, it was concluded that the Decision Support System Application Program to Determine the Best Employee Performance in the company can help the admin and manager in determining the best employee performance